Lâminas de água e adubação nitrogenada no crescimento e produção de gladíolos - Porto, Rebeca de Andrade (2012)
The gladiolus also known as Palma or Palma-de-Santa-Rita is a cut flower very common used for home decoration. The objective of this study was to evaluate the effect of replacement blades of water to field capacity (50, 75, 100, 125, 150%) and doses of nitrogen (0, 30, 60, 90, 120 mg dm-3) on the yield behavior of the culture in a protected environment. The specie studied was the Gladiolus x grandiflorus L., and its variety was Whitefriendship. The design was randomized blocks in 5x5 factorial design with four replications, totaling twenty and five treatments. The growth and yield of gladiolus was characterized by the variables: number of leaves, plant height, spike floral and floral stem length, number and diameter of flowers, floral stem dry matter, total dry weight, SPAD reading, stomatal conductance, number of days to silking and flowering, diameter and weight of bulbs, number and weight of bulblets. Results were submitted to analysis of variance by 5% probability by the F test, Pearson correlation and polynomial regression, using statistical software as Sisvar and Sanest for data analysis. It was observed effects of nitrogen fertilization only for variable dry flower stem weight. For replacement blades of water responses were significant for all parameters analysed. The irrigation management with replacement of the water levels above 75% of field capacity gave for the floral stem length a rating for commercial purposes. For the number of flowers replacement blades of water up of 100% provide commercial superior classification. The replacement blades of water up to 69% have produced bulbs with diameters of better yield potential. There was no need for nitrogen fertilization in the culture of gladiolus in Dystrophic Red soil from Savannah with the size of the plated bulb.